PiROB: Vision-based pipe-climbing robot for spray-pipe inspection in nuclear plants. (19th December 2018) - Kim, Jae-Hee; Lee, Jae-Cheol; Choi, You-Rack
Among many pipes in a nuclear power plant, the spray pipes in the reactor building are one of the most important pipes in view of their function and safety aspects. However, it is very difficult to manually reach and inspect the pipes for defects or damage, because these pipes are installed in very high places. To carry out this kind of inspection more easily, we developed a mobile robot to climb up and down and to cross over such pipes. A mobile robot should be small and light enough that it can be practically and safely operated in a nuclear power plant. Our robot is able to overcome obstacles such as valves, pipe flanges, and T-shaped branches, and it also meets the requirements of fail-safe, autonomous grasping, and self-power without the cables to the remote control station. The robot has a five-degree-of-freedom manipulator and two grippers and moves along the cylindrical pipes bypassing the obstacles. The robot should be able to grasp the next pipe autonomously, because the robot works in places high off the ground where the remote operator cannot see the next pipe for the robot to grasp. This article proposes a vision-based scheme for grasping a cylindrical pipe semi-autonomously and describes its solution along with the forward kinematics and inverse kinematics of the mobile robot. The configuration of the pipe-climbing robot, including its hardware and software, is described, and the robot control with visual grasping is explained. The robot can be used practically for spray-pipe inspection as well as many potential other applications, such as inspection of the roof frame of a stadium consisting of pipes.